2017
DOI: 10.1111/cen.13450
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism in patients with Graves’ hyperthyroidism

Abstract: Iron metabolism in patients with GH undergoes dynamic changes in patients with GH that resemble an acute-phase reaction. Inflammatory parameters and cytokines were unaffected by thyroid status. Gender and smoking status had an impact on ferritin, hepcidin and thyroid hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…It is possible that thyrotoxicosis uniformly results in a decrease in haemoglobin levels but in only relatively few patients is this drop large enough to result in anaemia. Similar to the recent small study by Fischli et al, 15 we also identified a reduction in ferritin levels as patients became euthyroid. Given the lack of association with inflammatory markers, 15 the elevated ferritin levels in thyrotoxicosis appears similar to that of SHBG to be a marker of thyrotoxicosis per se, rather than an acute phase response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is possible that thyrotoxicosis uniformly results in a decrease in haemoglobin levels but in only relatively few patients is this drop large enough to result in anaemia. Similar to the recent small study by Fischli et al, 15 we also identified a reduction in ferritin levels as patients became euthyroid. Given the lack of association with inflammatory markers, 15 the elevated ferritin levels in thyrotoxicosis appears similar to that of SHBG to be a marker of thyrotoxicosis per se, rather than an acute phase response.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the recent small study by Fischli et al, 15 we also identified a reduction in ferritin levels as patients became euthyroid. Given the lack of association with inflammatory markers, 15 the elevated ferritin levels in thyrotoxicosis appears similar to that of SHBG to be a marker of thyrotoxicosis per se, rather than an acute phase response. 16 Our study was limited in its ability to evaluate potential associations, as only 31 patients were anaemic and of these, most had pre-existing anaemia or a clearly defined underlying cause.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, polymorphisms in the IL-6 gene were found to be correlated with GD predisposition (21). It may be presumed that IL-6 overproduction in patients with GD stimulates the JAK2-STAT3 pathway to synthesize hepcidin, which consequently affects iron homeostasis and haematological parameters (12,22).…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes in hepcidin concentration take place along with the improvement of iron homeostasis parameters (10,11). So far, data concerning the role of hepcidin in hyperthyroidism are sparse and ambiguous, which might be related to the diverse aetiology and severity of thyroid disease among the studied participants (12,13). Thus, the aim of our study was to prospectively assess hepcidin serum concentration and other parameters related to Fe homeostasis in a well-characterized group of hyperthyroid patients exclusively in the course of GD at diagnosis and during remission.…”
Section: Introductionmentioning
confidence: 94%
“…Another hormone that plays an important role in iron metabolism is hepcidin, a systemic iron-regulatory hormone. Only in one study in nonpregnant women with Graves disease, hepcidin levels were correlated with TH, and they were lower in the euthyroid phase than in the hyperthyroid phase when measured with mass spectrometry [57]. No difference in hepcidin levels was found when measured with an ELISA method, and this methodological problem is one of the reasons why few studies investigated the relationship between hepcidin and thyroid function.…”
Section: New Candidate Variables Contributing To Variation In Thyroidmentioning
confidence: 99%